Methodology for Monitoring and Control of Finger Deformation in Patients with Arthritis Using Fractal Dimension - Auccahuasi, Wilver; Urbano, Kitty; Rojas, Karin; Benites, Nicanor; Meza, Sandra; Romero-Echevarria, Luis (International Journal of Online and Biomedical Engineering (iJOE), 2025)
Regenerative diseases, as is the case of arthritis, generate a change in the morphology of the fingers and toes; thus, as time passes, the joints of the fingers begin to deform, which causes a change in the morphology of the joints and fingers. One of the effects that is noticeable by patients is the pain that these deformations cause in addition to the deterioration of the maneuverability of objects with hands. In this article we present a method for the analysis of the fingers of the hands, through the analysis of images obtained through the photographic registration of the hand, then the value of the fractal dimension (FD) is obtained, to know the objective index for the measurement of the morphology of the hand, in this way it is possible to evaluate the deformation of the joints of the fingers, In this way it is possible to analyze and monitor the level of deformation, thus being able to improve the treatment. Due to having a record of the evolution of the deformations, we present as a result a demonstration of the methodology by analyzing the FD of the hands of a patient. The calculation of the FD was developed using the Matlab tool, which can be replicated and scaled according to the need of each situation.